A igreja como "pedacinho do Brasil": migrações e religião na capital do Texas - Jesus, Rodrigo Otávio Serrão Santana de (2014)
The main goal of this Master s thesis is to understand the existing dynamics between Brazilian evangelical churches in the city of Austin, Texas (USA) and its faithful. Thus, the main focus becomes the everyday activities that take place spontaneously within such institutions. These activities are: the processes of cultural maintenance, the social and support networks and forms of cultural assimilation, provided or restricted, within these churches. Combining these three activities inherent in the Brazilian evangelical churches in Austin, we have what we have called, the church as a piece of Brazil . We consider the characteristic of being a piece of Brazil as the greatest gift (MAUSS, 2003) that the Brazilian church can offer to Brazilians in Austin. The data collected in the field reveals that the church as a piece of Brazil serves, among other things, to delay the return of migrants to their homeland, or even make them think about permanently residing in the U.S. The research centers its theoretical and conceptual analysis from the diasporic and transnational studies. Then, investigates the data obtained in the field through interviews, surveys, and observation for thirty days.